National Youth Survey (United States): Wave IV, 1979 - Elliott, Delbert S. ([Verlag nicht ermittelbar], 1988)
Youth data for the fourth wave of the National Youth Survey are contained in this data collection. The first wave of this survey was conducted in 1976 (ICPSR 8375), the second wave in 1977 (ICPSR 8424), and the third wave in 1978 (ICPSR 8506). Data are available in this wave on the demographic and socioeconomic status of respondents, disruptive events in the home, youth aspirations and expectations, social isolation, normlessness, perceived disapproval by parents and peers, attitudes toward deviance, exposure and commitment to delinquent peers, sex roles, interpersonal violence, pressure for substance abuse by peers, self-reported delinquency, drug and alcohol use, and victimization.